An insight into the dependence of the deamination rate of human APOBEC3F on the length of single-stranded DNA, which is affected by the concentrations of APOBEC3F and single-stranded DNA - Wan, Li; Kamba, Keisuke; Nagata, Takashi; Katahira, Masato (Biochimica et biophysica acta. General subjects, 2020)
APOBEC3F (A3F), a member of the human APOBEC3 (A3) family of cytidine deaminases, acts as an anti-HIV-1 factor by deaminating deoxycytidine in the complementary DNA of the viral genome. A full understanding of the deamination behavior of A3F awaits further investigation. The real-time NMR method and uracil-DNA glycosylase assay were used to track the activities of the C-terminal domain (CTD) of A3F at different concentrations of A3F-CTD and ssDNA. The steady-state fluorescence anisotropy measurement was used to examine the binding between A3F-CTD and ssDNA with different lengths. The use of the A3F-CTD N214H mutant, having higher activity than the wild-type, facilitated the tracking of the reactions. A3F-CTD was found to efficiently deaminate the target deoxycytidine in long ssDNA in lower ssDNA concentration conditions ([A3F-CTD] ≫ [ssDNA]), while the target deoxycytidine in short ssDNA is deaminated efficiently in higher ssDNA concentration conditions ([A3F-CTD] ≪ [ssDNA]). This property is quite different from that of the previously studied A3 family member, A3B; the concentrations of the proteins and ssDNA had no effect. The concentrations of A3F-CTD and ssDNA substrates affect the ssDNA-length-dependence of deamination rate of the A3F-CTD. This unique property of A3F is rationally interpreted on the basis of its binding characteristics with ssDNA. The discovery of the unique property of A3F regarding the deamination rate deepens the understanding of its counteraction against HIV-1. Our strategy is applicable to investigate the other aspects of the A3 activities, such as those involved in the cancer development. •ssDNA cytidine deaminase activity of APOBEC3F (A3F) was investigated.•The A3F N214H mutant has a higher activity and facilitated the analyses.•The Real-time NMR and UDG assay tracked the activity at the different concentrations.•The concentrations of A3F and ssDNA affect the ssDNA length-dependent activity of A3F.•The ssDNA-binding characteristics of A3F rationally explained its unique activity.